2022
DOI: 10.1177/10732748221095955
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Mortality in Asian Countries: A Trend Analysis

Abstract: Background This study aimed to evaluate the updated burden and temporal trends of cancer incidence and mortality in Asian countries. Methodology The data used in this study were retrieved from the Global Cancer Observatory, Cancer Incidence in Five Continents volumes I-XI, and the World Health Organization mortality database. These data were used to calculate the Average Annual Percentage Change (AAPC), with a 95% confidence interval (CI) by joinpoint regression analysis to determine the epidemiological trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…According to our findings, the age-adjusted incidence rate of liver cancer increased from 2004 to 2015, and the incidence of stage I cases was significantly higher than other stages ( Figures 1 and 2 ). Since this significant amount of change was particular for stage I and occurred in a short period of time, it is unlikely to be the result of biological factors.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…According to our findings, the age-adjusted incidence rate of liver cancer increased from 2004 to 2015, and the incidence of stage I cases was significantly higher than other stages ( Figures 1 and 2 ). Since this significant amount of change was particular for stage I and occurred in a short period of time, it is unlikely to be the result of biological factors.…”
Section: Discussionsupporting
confidence: 55%
“…Liver cancer is one of the most frequent fatal malignancies worldwide [ 1 ] causing 830 000 deaths in 2020 [ 2 ]. The incidence of liver cancer demonstrates an increasing trend in developed countries and remains the eighth most common malignancy in women and fifth in men [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the study of Claros, Messa, and Perdomo (2019), the number of cancer-related deaths is expected to increase annually from 14 million in 2012 to 22 million after two decades [16]. In 2020, a study have shown that lung cancer is the most commonly diagnosed cancer in Asia, with 13.8% cases, breast cancer comes second, with 10.8% cases, followed by colon cancer with 10.6% cases, stomach cancer with 8.6% cases and lastly liver cancer with 6.9% cases [17]. Men are more likely to develop lung, stomach, liver, colon/rectum, and esophageal cancers, while women are more likely to develop breast, lung, stomach, colon/rectum, and liver cancers [18].…”
Section: Cancermentioning
confidence: 99%
“…Men are more likely to develop lung, stomach, liver, colon/rectum, and esophageal cancers, while women are more likely to develop breast, lung, stomach, colon/rectum, and liver cancers [18]. Moreover, a study of Huang et al (2022) also stated that the increase in urbanization, westernization, globalization, and common lifestyle habits, such as smoking, high-cholesterol foods, and alcohol consumption, are contributing factors to the burden of cancer in different countries of Asia [17]. According to Sankaranarayanan et al (2014) the emerging cases of this chronic disease requires utmost recognition, particularly from the government as it is also considered an important public health problem in Asia [18].…”
Section: Cancermentioning
confidence: 99%
“…The overall prevalence rates of adenoma (23.9%; 95% CI, 22.2-25.8%), advanced adenoma (4.6%; 95% CI, 3.8-5.5%), and CRC (0.4%, 95% CI, 0.3-0.5%) remain high worldwide [2]. Over the past decade, there has been an increasing trend of CRC incidence in Asian countries, which necessitates more intensive preventive initiatives [3]. CRC screening by fecal immunochemical tests (FITs) and colonoscopy has reduced CRC-related mortality by 33% and 68%, respectively [4][5][6].…”
Section: Introductionmentioning
confidence: 99%